Structural and functional characterization of the bacterial biofilm activator RemA - Tamara Hoffmann (Nature Portfolio, 2021)
Biofilm formation in Bacillus subtilis requires expression of matrix production genes, which are upregulated by transcriptional activator RemA. Here, the authors show that RemA forms octameric rings with the potential to form a 16-meric superstructure, suggesting that the protein can wrap DNA through a LytTR-related domain.